Interface Evolution of Solid Oxide Cells between the Electrode and the Interconnect Rib Induced with Applied Current. Issue 4 (24th February 2022) - Huang, Nan; Su, Yu; Han, Beibei; Guan, Wanbing; Singhal, Subhash C.
Abstract : Herein, the interface evolution of solid oxide cells (SOCs) on the interfacial contact resistance (ICR) between the electrode and the interconnect rib at different current densities is quantitatively studied using a stainless steel 430 (SUS430)/(La, Sr) (Co, Fe)O3 (LSCF)/SUS430 sandwich structure. To simulate the actual operation of SOCs, different current densities (200, 400, 600, 800, and 1000 mA cm −2 ) are applied to the sandwich structure by an external power supply and a DC electronic load. Experimental results show that, under an isothermal condition for 1012 h and a thermal cycling condition for 15 times, ICR is smaller when the current density is increased. This phenomenon may be due to the softening of the oxide film on the SUS430 interconnect rib and an increase in the contact area between the SUS430 interconnect rib and the electrode LSCF. Additionally, the microstructure, surface roughness, and contact theory are analyzed in detail. The results indicate that interface contact between the electrode and the interconnect rib may be improved with suitable applied current. This work provides the understanding of possible interface evolution of SOCs induced with applied current. Abstract : Herein, the interface evolution of solid oxide cells on the interfacial contact resistance (ICR) at different current densities is quantitatively studied using a SUS430/(La, Sr) (Co, Fe)O3 (LSCF)/SUS430 sandwich structure. The ICR between the SUS430 interconnect rib and the LSCF electrode slowly increases in the long term with current passing through the interface.